Multi-scale modeling and thermal transfer properties of electric heating fabrics system. Issue 6 (4th November 2019) - Yang, Yunchu; Qian, Jiangrui; Chen, Yang
Abstract : Purpose: The purpose of this paper is to investigate the thermal transfer properties of electric heating fabric system which contains heating units or conductive yarns by numerical simulation, in order to optimize and evaluate the thermal performance of heating clothing. Design/methodology/approach: Two kinds of FEM models are created by ANSYS system: macro-scale models of the fabrics system with heating units and air layer; and meso-scale models of the plain-woven fabrics were established embedded with the stainless yarns. In the macro-scale model, the interior and surface temperature field distribution were simulated and analyzed based on different heating unit size, heating power, heating region, air layer thickness and ambient temperature. For meso-scale models, the effects of the conductive yarns temperature, covering fabrics and pore-filling material on the temperature field distribution were simulated and analyzed. Findings: With the increasing of the air layer thickness or the effective conductivity, the heat transfer along the direction of fabric thickness decreases gradually. The heat transfer along the fabric plane can be increased by dispersing the heating region. With the increasing of the conductive yarns' temperature or the covering fabrics' conductivity, the heat transfer distance along the fabric warp direction can be increased. Filling the internal pores of the fabric with 10 wt% SiC/TPU hybrid materials can effectively increase the in-plane heat transfer and improve the temperature uniformity on the surface of heated fabrics. Originality/value: The finite element method was used to establish the simulation models of the heating fabric systems. The influence of several parameters on the thermal performance was analyzed and discussed, as well as the internal and external temperature distribution in the macro and micro scales models.